FE-SPH hybrid method to simulate the effect of tool inclination angle in oblique diamond cutting of KDP crystal - Zhang, Shuo; Zong, Wenjun (International journal of mechanical sciences, 2021)
•A FE-SPH hybrid model is used to simulate the oblique cutting of KDP crystal.•Hydrostatic pressure reflects the susceptibility of surface to cracks formation.•Chip flow angle in oblique diamond cutting follows the Stabler's chip-flow rule.•Phenomena of chip tearing and interference zone are relieved in oblique cutting.•Surface roughness depends on the competition of multiple influencing factors. Due to the soft and brittle characteristic, the potassium dihydrogen phosphate (KDP) crystal undergoes a complex process in diamond cutting, which makes the material removal mechanism is still a subject of controversy. In this paper, based on the machining model of oblique diamond cutting of KDP crystal, the effect of tool inclination angles in machining is numerically investigated by constructing a FE-SPH hybrid model, which combines the finite element (FE) method and smoothed particle hydrodynamics (SPH). Subsequently, oblique fly-cutting experiments with the same tool geometries and cutting parameters are performed, and the topographies of uncut shoulder and finally machined surface are measured by the atomic force microscope (AFM). Results show that the distribution of hydrostatic pressure clearly reflects the susceptibility of the processed surface to the cracks formation. With the consideration of hydrostatic pressure, the simulated results of cracks on the uncut shoulder and finally machined surface present a good consistency with the measured results in experiments. Moreover, the chip flow angle in simulation approximately follows the Stabler's chip-flow rule. As tool inclination angle increases, the width of interference zone decreases and the phenomenon of chip tearing is gradually relieved. Finally, the simulation results and experimental observations confirm that the roughness of finally machined surface is influenced by the average slope of uncut shoulder, the width of interference zone and the distribution of cracks. [Display omitted]